Industrial piping and equipment estimating manual - Storm, Kenneth (Gulf Professional Publishing, 2017)
Industrial Piping and Equipment Estimation Manual delivers an invaluable resource for day-to-day operations. Packed full of worksheets covering combined and simple cycle power plants, refineries, compressor stations, ethanol, hydrogen and biomass plants, this reference helps the construction engineer and estimator learn how to create bids where scope and quantity differences can be identified and project impacts estimated. Beginning with an introduction devoted to labor, productivity measurement, estimating methods, and factors affecting construction labor productivity and impacts of overtime, the author then explores equipment through hands-on estimation tables, including sample estimates and statistical applications. The book rounds out with a glossary, abbreviations list, formulas, and metric/standard conversions, and is an ideal reference for estimators, engineers and managers with the level of detail and equipment breakdown necessary for today's industrial operations.